(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Focal epilepsy is commonly associated with focal epileptogenic lesions and identification of these lesions are vital for management. Electroencephalogram (EEG) and Magnetic Resonance Imaging (MRI) of brain are commonly used neurodiagnostic procedures to localize the lesions. Objective: The study aims to observe the diagnostic yields of interictal EEG and MRI of the brain in the localization of focal epilepsy. Materials and Methods: This cross-sectional study was carried out in the Department of Neurology at National Institute of Neurosciences & Hospital (NINS&H), Dhaka from January, 2021 to June, 2022. A total number of 105 focal epilepsy patients were included in this study based on inclusion and exclusion criteria with ages above 12 years of both sex. Detailed history, clinical examination, EEG and MRI evaluation were done and recorded. Chi-Square test was performed to compare the EEG and MRI data and p value of <0.05 was considered significant. Results: The age range was 13 to 75 years with male female ratio of1.6:1. Mean age ofthe patients was 26.65±2.70(SD) years and the majority from the age group 18-30 years. Frequently found seizure type was focal to bilateral tonic-clonic (60, 57.10%). Abnormal EEG was found in 50.5% (n = 53) and abnormal MRI in 45.7% (n = 48) respondents. Both MRI and EEG were found abnormal in 21% of cases and in 24.8% of cases, both MRI and EEG were normal. With normal EEG findings, 24.8% of patients had abnormal MRI findings and 29.5% had abnormal EEG findings with normal MRI findings. No significant association was observed between EEG and MRI findings. Conclusion: A numberofMRI abnormalities were found in patients with normal EEG and vice versa. Our results did not reveal any correlation between EEG and MRI in the localization of epileptogenic lesions in focal epilepsy.